Effect of Postoperative Mechanical Axis Alignment on Survival and Functional Outcomes of Modern Total Knee Arthroplasties with Cement: A Concise Follow-up at 20 Years*. (21st March 2018) - Abdel, Matthew P.; Ollivier, Matthieu; Parratte, Sebastien; Trousdale, Robert T.; Berry, Daniel J.; Pagnano, Mark W.
Abstract : Abstract: We previously compared the 15-year survivorship of total knee arthroplasty (TKA) implants that were mechanically aligned (0° ± 3° relative to the mechanical axis) compared with those that were outside that range and considered outliers. The original publication included 398 TKAs (292 in the aligned group and 106 in the outlier group) performed from 1985 to 1990. At the time of follow-up in the previous study, 138 patients (155 TKAs) had died and 59 knees had been revised. Since that publication, 49 additional patients (87 knees) have died. At 20 years, 57 (19.5%) of the 292 knees in the mechanically aligned group had been revised compared with 16 (15.1%) of the 106 knees in the outlier group (p = 0.97). Postoperative alignment within 0° ± 3° of the mechanical axis did not provide a functional advantage at 1, 5, 10, 15, and/or 20 years postoperatively as demonstrated by the Knee Society scores being similar between the groups (p ≥ 0.2 at all intervals). At 20 years, we once again did not find that neutral mechanical alignment provided better implant survivorship than that found in the outlier group. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.